Improvement studentsâ activities and cognitive learning outcomes of Hasyim Asyâari University through guided discovery learning - Hayati, Nur; Berlianti, Ninda Ayu (Jurnal Pendidikan Biologi Indonesia, 2016)
Learning science is not only related to the acquisition of knowledge but also a process of discovery. Based on learning observations, it was known that the activities and cognitive learning outcomes of Science Education department students, Faculty of Education, Hasyim Asyâari University Jombang still low. Alternative learning that can be done to improve the activities and cognitive learning outcomes of students was guided discovery learning. This research was Classroom Action Research (PTK) with two cycles were carried out in the second semester of the 2015/2016 academic year. The research instruments were studentsâ activities assessment sheet, cognitive learning outcomes assessment sheet, learning observation sheet, and questionnaire responses of students to the learning process. Qualitative data were analyzed descriptively and quantitative data were analyzed by comparing the percentage studentsâ activities and cognitive learning outcomes in the cycle I and the cycle II. The result of this research were the percentage of studentsâ activities increased from 61,30% to 71,68%. Average of cognitive learning outcomes has increased from 73.68 to 80.04 and the percentage of cognitive achievement increased from 68.18% to 81.81%. The conclusion of this research was the guided discovery learning can improve the studentsâ activities and cognitive learning outcomes.Â